Reference intervals for red cell variables and platelet counts in infants at 2, 5 and 13 months of age: a cohort study. Issue 11 (13th July 2013) - Hinchliffe, R F; Bellamy, G J; Bell, F; Finn, A; Vora, A J; Lennard, L
Abstract : Aims: To derive reference values for red cell variables and platelet counts from a cohort of infants sampled at precise ages during the first 13 months of life. Methods: Blood counts, reticulocyte counts and zinc protoporphyrin concentrations were obtained from healthy term infants of North European ancestry at 2, 5 and 13 months of age. Results: Mean cell volume (MCV) and mean cell haemoglobin (MCH) values did not differ significantly between 5 and 13 months and MCH concentration was unaffected by age. Values of all other variables at any one age differed significantly from those at the other two. Haemoglobin, mean cell haemoglobin, zinc protoporphyrin and platelet values (95% ranges) at 2 (n=119), 5 (n=97) and 13 months (n=42) were, respectively, 91–125, 101–129 and 105–133 g/L; 28.6–33.1, 24.5–28.7 and 24.3–28.7 pg; 36–116, 25–91 and 27–57 micromol/mol haem; and 216–658, 241–591 and 209–455×10 9 /L. At 2 and 5 months, respectively, 26.9% and 10.8% of subjects had platelet counts >500×10 9 /L. Reticulocyte counts at 2 months and MCV and MCH values at 5 months were significantly higher in girls. In boys, red cell distribution width values were significantly higher at 5 months, and zinc protoporphyrin values at both 2 and 5 months. Conclusions: These findings indicate the value of obtaining reference data at precise ages during infancy and confirm and extend earlier reports indicating a gender difference in laboratory measures used to assess iron status in early infancy.